Re-narration in John Minford’s translation of Sun Tzu’s The Art of War - Zhang, Linyu; Mansor, Nor Shahila; Ghazali, Akmar Hayati Ahmad; Li, Mengduan (Hacettepe University, 2024)
In the field of translation studies, while re-narration is commonly observed in translated works, there is a noticeable lack of research focusing on re-narration specifically within wenyan translations. Addressing this gap, this study aims to investigate how re-narration occurs in wenyan translation through the framing strategies employed by translators, using Sun Tzu's The Art of War as a classical wenyan literary example in China. John Minford's 2002 translation is selected for analysis due to its publication in the 21st century and its inclusion of commentary to aid English readers in contextual understanding. The theoretical framework of Baker's Narrative Theory guides this examination. A sample of 671 translation instances from Chinese to English is analysed. The findings reveal that selective appropriation emerges as the primary framing strategy in commentary translation, while the repositioning of participants emerges as the most prominent framing strategy in re-narration.